Pengaruh Core Service Quality, Peripheral Service dan E-Health terhadap Kepuasan Pasien pada Rumah Sakit Umum Daerah di Kabupaten Halmahera Utara - Simone Petrusha Merielle Sumampouw; Yuanita Melina Anggoro; Cenny Hon; Ni Putu Ayu Paramitha Wedhasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Finding out how e-health, core service quality, and peripheral service quality impact patient happiness is the aim of this study. By using these criteria, it is expected that the North Halmahera District General Hospital will be able to address patient concerns. The study's sample consisted of 100 patients who had undergone treatment in the preceding six months. The study's sample was selected using a random sampling technique. The data analysis method used to investigate the relationship between e-health and patient happiness as well as the caliber of core and auxiliary services is multiple linear regression analysis. According to the study's findings, core service quality, peripheral services, and e-health all have a substantial impact on patient satisfaction at the North Halmahera District Hospital. Core service quality, peripheral services, and e-health all have a positive impact at the same time.